2021
DOI: 10.30872/psikoborneo.v9i2.5980
|View full text |Cite
|
Sign up to set email alerts
|

Konsep Diri Dan Dukungan Orangtua Terhadap Keputusan Karir

Abstract: Penelitian ini bertujuan untuk menguji secara empirik ada atau tidaknya pengaruh antara konsep diri dan dukungan orangtua terhadap keputusan karir pada siswa SMA, subjek penelitian ini adalah peserta didik di SMA Negeri 2 Tenggarong Seberang sebanyak 168 siswa. Skala disusun dengan skala model likert. Data yang terkumpul akan dianalisis dengan uji analisis regresi linear berganda dengan bantuan program Statistical Package for Social Sciences (SPSS) 25.0 for Windows. Hasil dari penelitian ini menunjukan bahwa: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
2
Order By: Relevance
“…Career selection is the first step in their career formation journey. Every individual has hopes and aspirations to achieve a promising career (Simbolon & Rasyid, 2021). To achieve their desired career, students need to be committed to continuously improving the quality and responsibility of their work.…”
Section: Career Decisionsmentioning
confidence: 99%
“…Career selection is the first step in their career formation journey. Every individual has hopes and aspirations to achieve a promising career (Simbolon & Rasyid, 2021). To achieve their desired career, students need to be committed to continuously improving the quality and responsibility of their work.…”
Section: Career Decisionsmentioning
confidence: 99%
“…Penelitian lain yang turut memperkuat hasil penelitian ini adalah penelitian Simbolon & Rasyid (2021). Melalui hasil penelitiannya terungkap bahwa konsep diri berpengaruh terhadap keputusan karier siswa.…”
Section: Hasil Dan Diskusiunclassified
“…Adapun keputusan karier merupakan tahapan akhir dalam penentuan karier yang tentunya diawali oleh perencanaan karier terlebih dahulu. Simbolon & Rasyid (2021) mengemukakan bahwa pemilihan karier merupakan implementasi dari konsep diri. Salah satu aspek konsep diri yang memiliki hubungan dengan perkembangan karier individu adalah efikasi diri (self-efficacy).…”
Section: Hasil Dan Diskusiunclassified
“…Thus, support from the closest people is essential in achieving success in various fields. Parental support has a significant role for children, including education and career choices (Amini & Salim., 2020;Sawitri et al, 2014;Simbolon & Rasyid, 2021). Studies on secondary students or college students in Asia showed that most people choose education majors and occupations following their parents' expectations (Leong et al, 2010;Sawitri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%